2015
DOI: 10.1021/acsami.5b04496
|View full text |Cite|
|
Sign up to set email alerts
|

Fabrication of Microcapsules for Dye-Doped Polymer-Dispersed Liquid Crystal-Based Smart Windows

Abstract: A dye-doped polymer-dispersed liquid crystal (PDLC) is an attractive material for application in smart windows. Smart windows using a PDLC can be operated simply and have a high contrast ratio compared to those of other devices that employed photochromic or thermochromic material. However, in conventional dye-doped PDLC methods, dye contamination can cause problems and has a limited degree of commercialization of electric smart windows. Here, we report on an approach to resolve dye-related problems by encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 36 publications
0
62
0
Order By: Relevance
“…[14] Electrically switched guest-host devices have also been suggested for use within applications outside of displays, such as in smart windows using polymerdispersed liquid crystal hosts that enable the transmittance of the windows to be electrically controlled. [15] Incorporating fluorescent dye molecules into these smart windows, and using the windows themselves as waveguides, potentially enables light absorbed by the windows in their absorbing state to be used for solar energy conversion. [16] Combining the optical properties of chiral nematic liquid crystals with the absorption properties of guest dye molecules has also lead to electrically switched laser protection devices being developed.…”
Section: Introduction To Guest-host Systemsmentioning
confidence: 99%
“…[14] Electrically switched guest-host devices have also been suggested for use within applications outside of displays, such as in smart windows using polymerdispersed liquid crystal hosts that enable the transmittance of the windows to be electrically controlled. [15] Incorporating fluorescent dye molecules into these smart windows, and using the windows themselves as waveguides, potentially enables light absorbed by the windows in their absorbing state to be used for solar energy conversion. [16] Combining the optical properties of chiral nematic liquid crystals with the absorption properties of guest dye molecules has also lead to electrically switched laser protection devices being developed.…”
Section: Introduction To Guest-host Systemsmentioning
confidence: 99%
“…It has been observed that the contrast ratio of a PDLC is improved with the addition of dye. 23,24 When a dye (guest) is added to the LCs (host), it gives rise to a guest-host (G-H) conguration, and it leads to the formation of guest-host PDLCs (GHPDLCs). 25 In such systems, the orientation of dye molecules is controlled by the LCs in an applied electric eld, but the dye molecules in a polymer matrix are not affected by the eld.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Stupp et alr eporteds elf-assembly of quinquethiophenesf unctionalizedw ith b-sheet formingp eptide, which formed 1D nanostructure in aqueouss olution. [40] Successfula pplicationso fe lectrochromicd evices (ECD) [41][42][43][44] include smarts unglasses, [45][46] smart-window, [47][48][49] stretchablee lectronic skin, [50] ande lectrochromic displayd evices. [51] Among the varietieso fs mall molecular and polymerico rganic electrochromic materialsu sedi ne lectrochromic devices, oligothiophenesa sw ella s polythiophene derivatives area ni mportant classo fp-conjugated organic material.…”
Section: Introductionmentioning
confidence: 99%